Significance of Bank Specific and Macroeconomic Determinants on Performance of Indian Private Sector Banks - Aspal, Parvesh Kumar; Dhawan, Sanjeev; Nazneen, Afroze (International Journal of Economics and Financial Issues, 2019)
A sound financial system has vital influence on the economic development of a country. Banking system constitutes an important component of the financial system of the country; therefore, the economic importance of banks may not be underestimated. Performance evaluation of the banking system is an effective measure and indicator to check the strength of financial system of an economy. The overall objective of the present study was to explore the influence of bank specific factors and macroeconomic factors on the performance of private sector banks in India. To examine the effect of external or macroeconomic factors, growth rate of GDP and average annual inflation rate were considered. For the analysis, seven year panel data of 20 private sector banks was analyzed using linear multiple regression model. The financial performance of banks was expressed by Return on Assets variable. Using multiple regression technique the analysis of sample data for the time period 2008-2014 revealed that except capital adequacy ratio variable all other bank specific variables (Asset Quality, Management Efficiency, Earning Quality and Liquidity) and macroeconomic variable gross domestic product had significantly influenced the financial performance of sample banks in India and inflation was statistically insignificant in case of its effect on return on assets. The implications of the study revealed that inspite of optimum capital adequacy ratio maintained by private sector banks, the other variables related with management and governance of banks had significant effect on the financial performance of the banks. Keywords: Capital Adequacy Ratio, Asset Quality, Management Efficiency, Earning Quality, Liquidity, GDP, Inflation JEL Classifications: G21, G24, G28 DOI: https://doi.org/10.32479/ijefi.7727